Dietary intake of polyphenols and total antioxidant capacity and risk of prostate cancer: A case–control study in Iranian men. (11th November 2020) - Ghanavati, Matin; Clark, Cain C. T.; Bahrami, Alireza; Teymoori, Farshad; Movahed, Mehdi; Sohrab, Golbon; Hejazi, Ehsan
Abstract: Background: Prostate cancer (PCa) is one of the leading causes, globally, of cancer‐related mortality. Previous studies have reported an inverse relationship between some food items or dietary patterns and prostate cancer risk. Polyphenols, as antioxidant and anti‐inflammatory dietary components, have been associated with a reduced risk of PCa, whilst dietary indices such as total antioxidant capacity are good predictors of PCa risk. Objective: The purpose of this study was to conduct a case–control study on the association between polyphenol intake and DTAC (dietary total antioxidant capacity) and PCa risk in men. Method: 205 hospital‐based controls and 97 newly diagnosed PCa patients were asked about their dietary intakes using a validated questionnaire. The polyphenol contents (flavonoids, lignans, stilbenes and phenolic acids) of foods and beverages were calculated. TAC was obtained using a comprehensive database consisting of the total antioxidant content of more than 3000 food and beverages. Logistic regression was used to determine the odds ratios (OR), with 95% confidence intervals (CI), of PCa according to categories of polyphenol intake and TAC. Results: When comparing the highest and the lowest tertile of total polyphenol (OR: 0.12; 95% CI: 0.03–0.41), lignans (OR: 0.14; 95% CI: 0.04–0.41), phenolic acids (OR: 0.18; 95% CI: 0.05–0.57) and some flavonoid subgroups intake including flavan‐3‐ols (OR: 0.24; 95% CI: 0.08–0.67), flavanones (OR: 0.10; 95% CI: 0.03–0.31) and flavones (OR: 0.33; 95% CI: 0.12–0.87), we observed a significant decreasing trend in the risk of PCa (p for trend<0.05). Conclusion: The results suggest that the consumption of some polyphenols can significantly reduce the risk of PCa.